2015
DOI: 10.1097/md.0000000000000723
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Preoperative Biliary Drainage Methods on Complications Following Pancreaticoduodenectomy

Abstract: The objective of this study was to investigate the effects of different preoperative biliary drainage (PBD) methods on complications in jaundiced patients following pancreaticoduodenectomy. We retrospectively analyzed 270 extrahepatic bile duct cancer patients who underwent pancreaticoduodenectomy. A total of 170 patients without PBD treatment were defined as the non-PBD group. According to different PBD methods, 45, 18, and 37 patients were classified into the percutaneous transhepatic biliary drainage (PTBD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 32 publications
1
37
0
1
Order By: Relevance
“…Three studies [89,11] reported that ENBD decreased the incidence of preoperative cholangitis before standard resection or palliative surgery compared with EBS, while no significant association was reported in 4 studies. [10,1214] Moderate heterogeneity ( I 2  = 31%, P  = 0.19) was found, so we chose a random-effect model to pool the OR. Overall, the pooled data demonstrated that ENBD was associated with a low incidence of preoperative cholangitis (OR = 0.35, 95% CI = 0.25–0.51, P  < 0.0001) in the MBO patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies [89,11] reported that ENBD decreased the incidence of preoperative cholangitis before standard resection or palliative surgery compared with EBS, while no significant association was reported in 4 studies. [10,1214] Moderate heterogeneity ( I 2  = 31%, P  = 0.19) was found, so we chose a random-effect model to pool the OR. Overall, the pooled data demonstrated that ENBD was associated with a low incidence of preoperative cholangitis (OR = 0.35, 95% CI = 0.25–0.51, P  < 0.0001) in the MBO patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Data from 5 articles, [810,1213] including 367 cases in the ENBD group and 381 cases in the EBS group, were used in this meta-analysis. All 5 studies reported that there was no significant difference in the incidence of preoperative pancreatitis between the ENBD and EBS groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,8 The three commonly used methods for achieving preoperative biliary drainage includes endoscopic retrograde biliary stent placement (ERBS), endoscopic nasobiliary drainage (ENBD) and percutaneous transhepatic biliary drainage. 9 The endoscopic positioning of a biliary endoprosthesis has become a relatively easy procedure for experienced endoscopists. Late cholangitis occurred only in case of dislodgement or clogging of the endoprosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al found that PTBD can improve surgical outcomes by reducing severe complication rate in jaundice patients following pancreaticoduodenectomy. 9 In this case, open bilio-digestive bypass was performed instead of preoperative biliary drainage. Whipple procedure (pancreaticoduodenectomy) was not performed, because the tumor size was more than 3 cm and there were metastases to the liver and peritoneum.…”
Section: Discussionmentioning
confidence: 99%